Hubungan Antara Kedisiplinan Kerja dan Kinerja Karyawan pada Perusahaan PT. TVS Motor Motor Company Indonesia (International Forum of Researchers and Lecturers, 2025)
This study aims to explore the relationship between work discipline and employee performance at PT. TVS Motor Company Indonesia. Work discipline is one of the key factors influencing the achievement of work targets and the improvement of employee productivity. This research uses a qualitative method with a descriptive approach. Data were collected through in-depth interviews, observations, and document studies with employees of PT. TVS Motor Company Indonesia. The results show that there is a strong relationship between work discipline and employee performance. A high level of discipline is reflected in punctual attendance, compliance with company regulations, and a strong sense of responsibility, all of which have a positive impact on performance achievement. These findings are expected to serve as a basis for management in formulating policies to foster work discipline and continuously improve employee performance.